KEANEKARAGAMAN FAUNA ENDEMIK DI TAMAN NASIONAL KELIMUTU KABUPATEN ENDE - Yosephina Payu Wao; Donatus Rendo (LPPM Universitas Cipta Mandiri, 2026)
This study aims to examine the diversity of endemic fauna found in the Kelimutu National Park area. The method used in this study is a qualitative research method with a literature review approach to examine the biodiversity of endemic fauna in the Kelimutu National Park area of ​​Ende Regency. The results of the study indicate that the diversity of endemic fauna in the area is a habitat for a number of endemic animals that are of high ecological value, such as the Great Rat (Papagomys armandvillei), Lawo Rat (Rattus hainaldi), Flores Eagle (Nisaetus floris) and Flores Mouse Deer (Pachycephala nudigula). The results of the literature review indicate that Papagomys armandvillei is an endemic rodent of Flores Island that has a relatively large body size, with a body length reaching 40–50 cm. Rattus hainaldi is an endemic rodent species found only on Flores Island that has distinctive characteristics including reddish-brown back hair, a white belly, and a tail that is longer than the head and body (around 110–130% of body length). Nisaetus floris is a raptor endemic to Flores Island with a body length ranging from 71-82 cm. Pachycephala nudigula is characterized by its ability to produce more than 16 different sounds, and the males have a red wattle on the front of their necks.